0708 Sleep and Daytime Dysfunction Among Women Veterans: The Impact of Caregiving. (27th April 2018) - Song, Y; Fung, C H; McGowan, S; Jouldjian, S; Josephson, K R; Mitchell, M N; McCurry, S M; Irwin, M R; Teng, E; Alessi, C A; Martin, J L
Abstract: Introduction: Most caregivers (i.e., those who regularly provide care for another person because of physical illness, memory disorder, psychological disorder, or physical health decline) are women, and prior research suggests the caregiving role is associated with negative health outcomes. Sleep problems are common in women, but less is known how caregiving affects specific sleep complaints and related daytime dysfunction, particularly in the growing population of women veterans. The purpose of this study was to compare self-reported sleep complaints and daytime dysfunction between women veteran caregivers and non-caregivers Methods: Secondary analyses were performed with data from a large regional postal survey about sleep in women veterans. Survey items included questions addressing insomnia diagnostic criteria (DSM-5), items from the Insomnia Severity Index and the Pittsburgh Sleep Quality Index, ICSD-3 sleep-related daytime consequences (e.g., fatigue, less motivation, difficulty with daily activities, trouble paying attention), self-rated health, pain, and demographic information, in addition to several items to identify caregiver status. T-test and chi-square were used to compare sleep characteristics and daytime dysfunction between caregivers and non-caregivers. Regression analysis tested whether caregiving status predicted sleep-related daytime dysfunction, adjusting for other characteristics. Results: Of 1, 475 respondents (mean age = 51.6 [SD 16.1] years, 48% non-Hispanic white), 261 (18%) were caregivers. Caregivers were less satisfied overall with their sleep, had more trouble staying asleep, and lower total sleep time than non-caregivers (all p < 0.05), but no difference in the prevalence of survey reported symptoms of insomnia. Caregivers also experienced more symptoms of daytime dysfunction from poor sleep (p=0.02). Being a caregiver significantly predicted daytime dysfunction, even after adjusting for age, pain, and health status (model: p<0.001, adjusted R 2 =0.30). Conclusion: Caregiving status is associated with more sleep complaints in women veterans, and predicts worse daytime consequences of poor sleep. Further research is needed to understand the relationship between caregiving and disturbed sleep among women veterans and to develop interventions to address the needs of this growing population. Support (If Any): HSR&D IIR 13-058-2; VA Greater Los Angeles Healthcare System GRECC; NIA K23AG055668.